The Effect of Self-Talk on Increasing the Self-Confidence of Pencak Silat Athletes - Natasya Arifah; Mulyana; Muhamad Tafaqur (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to examine the effect of self-talk training on improving the self-confidence of Pencak Silat athletes. Self-confidence is an essential psychological factor influencing athletic performance, while self-talk is a mental training technique that helps regulate thoughts and emotions through positive internal dialogue. This study employed a one-group pretest-posttest experimental design involving 21 Pencak Silat athletes from Junior high school  46 Jakarta. The intervention consisted of eight self-talk sessions over four weeks focusing on education, practice, and reflection. Data were analyzed using SPSS 26. The average self-confidence score at the pretest was 33.52 with a standard deviation of 3.842, while at the posttest it increased to 38.57 with a standard deviation of 3.501. The Shapiro-Wilk normality test showed that both pretest and posttest data were normally distributed (p > 0.05), and the Levene’s Test indicated homogeneous variance (p = 0.567). The paired sample t-test produced a significance value of p = 0.000, indicating a significant difference between pretest and posttest results. These findings demonstrate that self-talk training effectively increases athletes’ self-confidence, emotional control, and focus, making it a practical psychological strategy to improve mental readiness and performance in Pencak Silat athletes.